2021
DOI: 10.1016/j.pneurobio.2021.102115
|View full text |Cite
|
Sign up to set email alerts
|

Towards a unified neural mechanism for reactive adaptive behaviour

Abstract: Surviving in a natural environment requires animals to sense sudden events and swiftly adapt behaviour accordingly. Such Reactive Adaptive Behaviour (RAB) has been characterized within a number of research fields, all orbiting around movement science but progressing in parallel, with little or no cross-field fertilization. We provide a concise review of these research streams, independently describing four types of RABs: (1) cortico-muscular resonance, (2) stimulus locked response, (3) online motor correction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 107 publications
2
12
0
Order By: Relevance
“…We suggest that the IMS we observed derives from fast and unintentional physiological responses to partners’ body movements, which could have been processed as salient stimuli, i.e., sudden stimuli that are likely to catch an observer’s attention. 58 , 59 , 60 , 61 , 62 Indeed, the body movements produced by our participants followed a sharp and fast-rising profile that could act as a synchronizing signal (for an example, see Figure 1 C). Notably, previous neurophysiological studies have demonstrated that salient stimuli with a fast-rising profile trigger fast behavioral responses, 63 , 64 , 65 , 66 , 67 , 68 which could potentially facilitate the emergence of IMS.…”
Section: Discussionmentioning
confidence: 82%
“…We suggest that the IMS we observed derives from fast and unintentional physiological responses to partners’ body movements, which could have been processed as salient stimuli, i.e., sudden stimuli that are likely to catch an observer’s attention. 58 , 59 , 60 , 61 , 62 Indeed, the body movements produced by our participants followed a sharp and fast-rising profile that could act as a synchronizing signal (for an example, see Figure 1 C). Notably, previous neurophysiological studies have demonstrated that salient stimuli with a fast-rising profile trigger fast behavioral responses, 63 , 64 , 65 , 66 , 67 , 68 which could potentially facilitate the emergence of IMS.…”
Section: Discussionmentioning
confidence: 82%
“…This appears to be the case for express saccades, which rely on the integrity of the midbrain superior colliculus (SC) and are potentiated by, but not critically reliant on, input from fronto-parietal circuits (Schiller et al, 1987;Edelman and Keller, 1996;Dorris et al, 1997;Dash et al, 2018Dash et al, , 2020. Although the SC has been implicated in mid-flight reach corrections (Day and Brown, 2001;Pruszynski et al, 2016;Reschechtko and Pruszynski, 2020;Suzuki et al, 2022) and interceptions of rapidly moving targets (Perfiliev et al, 2010), debates remain about the comparative role of subcortical versus cortical areas in expedited visually-guided reaching (Fautrelle et al, 2010;Gaveau et al, 2014;Novembre and Iannetti, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Coping with the ever-changing nature of the surrounding environment, the human brain has developed the capacity to initiate rapid and adaptive behavioral responses to salient sensory stimuli, with none or scarce influence of volition. We recently referred to this as Reactive Adaptive Behavior (RAB): salient sensory stimuli elicit fast involuntary behavioral responses that are, however, flexible on the basis of the current environmental context (1).…”
Section: Introductionmentioning
confidence: 99%
“…Second, CMR is adaptive, e.g. the amplitude of the force modulations is enhanced if the eliciting stimulus has high behavioral relevance (1).…”
Section: Introductionmentioning
confidence: 99%